China's evolving approach to peacekeeping - Lanteigne, Marc.; Hirono, Miwa. (London : Routledge, 2012)
'China has become a supporter of and contributor to UN peacekeeping. Is China's participation in peacekeeping likely to strengthen the current international peacekeeping regime by China's adopting of the international norms of peacekeeping? Or, is it likely to alter the peacekeeping norms in a way that aligns with its own worldview? And, as China's international confidence grows, will it begin to consider peacekeeping a smaller and lesser part of its international security activity, and thus not care so much about it? This book aims to address these questions by examining how the PRC has developed its peacekeeping policy and practices in relation to its international status. It does so by bringing in both historical and conceptual analyses and specific case-oriented discussions of China's peacekeeping over the past twenty years. The book identifies the various challenges that China has faced at political, conceptual and operational levels and the ways in which the country has dealt with those challenges and considers the implication of such challenges with regards to the future of international peacekeeping'--P. [i].
Introduction : China and UN peacekeeping / Miwa Hirono and Marc Lanteigne -- Principles and praxis of China's peacekeeping / Chin-Hao Huang -- Why does China participate in intrusive peacekeeping? : understanding paternalistic Chinese discourses on development and intervention / Shogo Suzuki -- A responsible power? : China and the UN peacekeeping regime / Courtney J. Richardson -- The responsibility to protect and China's peacekeeping policy / Sarah Teitt -- A change in perspective : China's engagement in the East Timor UN peacekeeping operations / Marc Lanteigne -- China's charm offensive and peacekeeping : the lessons of Cambodia--what now for Sudan? / Miwa Hirono -- Two pillars of China's global peace engagement strategy : UN peacekeeping and international peacebuilding / Zhao Lei.
'This book is a reproduction of International Peacekeeping, vol. 18, issue 3'--T.p. verso.
Includes bibliographical references (pages 121-135) and index.
Keywords: Peace-building -- China; China -- Foreign relations -- 1976-